Critérios de ressecabilidade dos tumores neuroblásticos: comparação entre o critério tradicional e os fatores de risco baseados na imagem. - Penazzi, Ana Claudia Soares [UNIFESP] (2016)
Objectives: Evaluate the casuistry of the Support Group for Adolescent and Children with Cancer of São Paulo, from January 2000 to May 2015, comparing resectability criteria used in the past, with the current resectability criterion through evaluation of radiological images at diagnosis and presurgical, applying risk factors defined by tomography and or resonance imaging. Correlate resectability, surgical complications and relapse, as well as evaluation of patients who remain alive. Methods: Retrospective study of service casuistry in the period determined in patients with neuroblastoma stages 3 and 4, tumor located in the abdomen and pelvis and imaging tests to diagnosis and preoperative. Twenty-seven patients were selected for the study after the selection criteria and with presence or absence of risk factors at diagnosis and preoperative was evaluated through tomography and magnetic resonance imaging. The data were statistically analyzed by the SPSS 20.0 and STATA 12 programs, the Kappa coefficient in the evaluation of the agreement between resectability criteria by the International Neuroblastoma Staging System and Image-defined risk factors, McNemar in the comparison of resectability to diagnosis and post-chemotherapy and significance level of 5% for all tests. Results: 27 children were analyzed with mean age at diagnosis of 2.5 years, where 55.6% were older than 18 months; 51.9% female sex and 66.7% had staging 4. There was concordance between the results of resectability by INSS and IDRFs at diagnosis (p = 0.007) and post-chemotherapy (p = 0.019), but there was no concordance between the results by IDRFs in the two moments. The patients classified as resectable by IDRFs after chemotherapy, all had complete resection and, on the other hand, those classified as nonresectable, 87.5% had incomplete tumor resection. At follow-up, 77.8% of the alive patients were in remission, 18.5% relapsed and 33.3% deaths. Conclusions: Resectability results were similar in both the traditional and IDRF methods at diagnosis and post-chemotherapy, preoperative QT increased tumor resectability, decreasing the number of IDRFs between diagnosis and post-QT (14,8% -34.6%), the presence of at least 1 IDRF was associated with incomplete resections (sensitivity 87.5%), complications were irrelevant as the number of relapses.